THE ANALYSIS OF SOCIAL MEDIA INFLUENCER TASYA FARASYA'S CREDIBILITY ON PURCHASE INTENTION FOR SKINCARE PRODUCTS WITH BRAND IMAGE AS A MEDIATING VARIABLE - Anita Septiani; Asep Muhamad Ramdan; Sopyan Saori (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This research explores the influence of social media influencer credibility, focusing on Tasya Farasya, on purchase intention toward skincare products, with brand image as a mediating variable. The study was conducted among female TikTok users in Sukabumi, aged 13 to 45, who had never used but were aware of the skincare brand Glad2Glow (G2G). Using a quantitative approach and associative method, 150 respondents were selected through purposive sampling. Data was collected via an online questionnaire and analyzed using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method. The study found that influencer credibility, consisting of expertise, trustworthiness, and attractiveness, has a significant and positive effect on brand image and purchase intention. Moreover, brand image was proven to significantly mediate the relationship between influencer credibility and purchase intention. This indicates that a credible influencer not only directly influences consumer buying interest but also enhances the perceived image of the brand, which further motivates purchasing decisions. The research highlights the vital role of credible influencers in digital marketing strategies. When influencers are perceived as knowledgeable, trustworthy, and appealing, they can build a strong brand image that positively influences consumer behavior. These findings are relevant for marketers and businesses in optimizing influencer marketing campaigns, especially in the beauty and skincare industry where consumer trust and brand perception play critical roles in purchasing decisions. Overall, the study contributes both theoretically and practically by offering insights into the mechanisms through which influencer credibility influences consumer intention through brand image formation.